From the Margins of the Periphery: Female Voices from Brazil´s and Portugal´s Hip Hop Scene - Lupati, Federica (2020)
This research responds to the need to fill the void in terms of studies and scholarships on female rappers from Portugal and Brazil. Addressing issues such as racism, patriarchy, male hegemony and the silencing or underestimation of women’s contributions to the building and evolution of rap both in Portugal and Brazil, the aim is to offer a space where these issues can be discussed, while also acknowledging and understanding the works and experience of female performers. In addition to this, the present work aims at discussing the social, cultural and politcal importance of hip hop as a marginal, yet global, contemporary practice and its evolution into a mass-mediatic culture. Hip hop’s contribution to the building of new individual and collective identities, its unapologetic narratives and revolutionary messages are here understood as tools that contribute to the understanding of the dynamics that agitate the social and creative realities of today’s post-modern and post-colonial world. Through a methodological approach that looks at interdisciplinarity as its main feature, this work borrows its core ideas from fields such as Cultural Studies, Hip Hop Studies, Gender Studies, Feminist Theory, among many others, as well as from the informal conversations that I have been recording throughout these years with Portuguese rappers Capicua, Telma TVon, Mynda Guevara, and Brazilian rappers Samantha Muleka, Rose MC, Keli Rosa and Sharylaine. Despite the fact some interviews did not make it to this final text, they were all fundamental to it.